Quality of Serious Illness Communication with Hospitalized Limited English Proficient Patients: A Mixed Methods Study - Laura M. Holdsworth; Samantha M. R. Kling; Marcy Winget; Heather Z. Mui; Donn W. Garvert; Darlene Veruttipong; Briththa Seevaratnam; Sonia Harris; Winifred Teuteberg (Palliative Medicine Reports)
Background: The Serious Illness Conversation Guide was developed to support high quality goals of care conversations with seriously ill patients; however, guide implementation for patients with limited English proficiency (LEP) has not been studied. This evaluation aimed to explore serious illness conversations with hospitalized LEP patients, defined as those with a non-English language documented, from clinician and interpreter perspectives; and assess differences in documentation in the electronic medical record (EMR) as a quality improvement effort. Methods: Parallel mixed methods evaluation including thematic analysis of observations and interviews with medical interpreters (n = 14), occupational therapists (n = 9), registered dietitians (n = 6), and resident physicians (n = 3) of a quaternary academic hospital in the United States. Comparison of EMR documentation for hospital admissions with English proficient (N = 7396) and LEP patients (N = 2326). Results: Six themes characterized serious illness communication and guide use with LEP patients. As compared to other clinical encounters, both interpreters and clinicians perceived serious illness communication as unique. Both groups acknowledged that interpreters convey meaning, though being an effective voice of the clinician required advanced preparation of the interpreter, even when the guide was used. There were no differences in documentation between the groups (4.7% (345/7396) versus 5.4% (126/2326); p = 0.21). Conclusions: Even when the guide is used, there may be differences in serious illness communication quality with LEP patients depending on how clinicians engage with the guide and interpreter preparation. The guide may be a method to enhance communication quality, but for LEP patients, requires the parallel implementation of workflows that support high-quality communication.